2013
DOI: 10.1016/j.febslet.2013.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin and metavinculin: Oligomerization and interactions with F‐actin

Abstract: a b s t r a c tVinculin, and its splice variant metavinculin, are scaffolding proteins that localize to cellular adhesions. Vinculin is a key player in mediating cell adhesion, motility, and cellular response to force. In the past decade, a number of new studies have evaluated the importance of vinculin oligomers, especially in their role of bundling F-actin. Emerging evidence also suggests that vinculin oligomerization is important for vinculin's scaffolding function. Here we describe the latest findings on v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 88 publications
1
27
0
Order By: Relevance
“…This structural change accounts for the altered tilt and twist of cofilin decorated filaments observed by EM 60,61 , Cryo-EM 59 and AFM 40 . No such tilt and twist in actin filaments decorated with MVT is observed by EM 7,12 . This is consistent with our finding that the D-loop and other structures are only mildly altered when actin is decorated with MVT.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This structural change accounts for the altered tilt and twist of cofilin decorated filaments observed by EM 60,61 , Cryo-EM 59 and AFM 40 . No such tilt and twist in actin filaments decorated with MVT is observed by EM 7,12 . This is consistent with our finding that the D-loop and other structures are only mildly altered when actin is decorated with MVT.…”
Section: Discussionmentioning
confidence: 83%
“…The helices are flanked by a so-called N-terminal strap and C-terminal arm, which interact with each other and a subset of the VT helices. The VT can dimerize in a number of configurations, one of which relies on a cryptic binding site that is revealed upon binding to actin and results in bundling 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The loss of Vinculin inhibits cell adhesion and diffusion. The absence of this protein results in lower cell dissemination on the material to be assessed and scarce formation of focal adhesions [27]; therefore, the images obtained in this study demonstrated that the group treated with MTA exhibited the lowest expression of Vinculin.…”
Section: Discussionmentioning
confidence: 90%
“…The structure of the actin-induced Vt dimer (reviewed in ref. 58 ) remains an important subject for future investigations.…”
Section: Discussionmentioning
confidence: 99%